Adsorption of dark coloured compounds from peach pulp by using granular activated carbon - Arslanoglu, FN; Kar, F; Arslan, N (Elsevier Sci Ltd, 2005)
The adsorption of dark coloured compounds from peach pulp on granular activated carbon (GAC) was studied at different GAC concentrations (0.5, 1, 3, 5 kg GAC per m(3) peach pulp) and the temperature range of 20-60 degrees C. The equilibrium isotherm for each dark coloured compounds-GAC system was determined. Absorbance data at 420 nm were used to plot all the isotherms that are correlated reasonably well with the Langmuir, Freundlich, Temkin and Frumkin isotherms. The characteristic parameters for each isotherm were determined. The Langmuir isotherm provided the best correlation for the dark coloured compounds. Five kinetic models were evaluated to fit the experimental data: the pseudo-first-order, the pseudo-second-order, the modified Freundlich, the pore diffusion and the Elovich equations. The kinetic parameters of each model were calculated. From the experimental results obtained, the adsorption process can be well described with the Elovich model for adsorption kinetics. The calculated activation energy for process studied was 9.83 kJ/mol. This low activation energy value indicates that the adsorption process is also diffusion controlled. (c) 2004 Published by Elsevier Ltd.
Keywords: peach pulp; adsorption; discolouration; granular activated carbon